A Cross-National Perspective on Unemployment and First Births - Christian Schmitt (European Journal of Population, 2012)
This article investigates the impact of unemployment on the likelihood of having a first child. Using micro-data from the European Community Household Panel, I apply event history methods to analyze first-birth decisions in France, West Germany, and the UK (1994–2001). The results highlight weak negative effects of unemployment on family formation among men, which can be attributed to the inability to financially support a family. Among women, unemployment exerts a positive effect on the propensity to have a first child in Germany and the UK, where institutional settings aggravate work–family conflicts. Unemployment increases the likelihood of family formation among women with a moderate or low level of education. This does not, however, generally apply to French women or to highly educated women in Germany and the UK, who, when unemployed, favor a quick return to work over motherhood. – – Cet article examine l'impact du chômage sur la probabilité d'avoir un premier enfant. A partir des données du Panel Communautaire européen des ménages, des méthodes biographiques sont utilisées afin d'analyser les décisions de la survenue d'une première naissance en France, en Allemagne de l'Ouest et au Royaume-Uni (1994–2001). Les résultats soulignent les faibles effets négatifs du chômage sur la constitution de la famille pour les hommes, qui peuvent être attribués à l'incapacité de soutenir financièrement une famille. En ce qui concerne les femmes, le chômage a un effet positif sur la probabilité d'avoir un premier enfant en Allemagne et au Royaume-Uni, pays où les contextes institutionnels aggravent les conflits entre travail et famille. Le chômage augmente la probabilité de constitution de la famille parmi les femmes ayant un niveau d'instruction faible ou modéré. Cependant, ce résultat n'est pas observé pour les françaises, ainsi que pour les femmes ayant un niveau d'instruction élevé en Allemagne et au Royaume—Uni. Pour ces dernières, lorsqu'elles sont au chômage, la reprise du travail serait prioritaire.
Additional information: The final publication is available at www.springerlink.com: http://dx.doi.org/10.1007/s10680-012-9262-5
Keywords: J13; J24; J64; C41; 330; Fertility; First birth; Cross-national comparison; Unemployment; Welfare states; Fécondité; Première naissance; Comparaison transnationale; Chômage; Etat providence; Familie; Arbeitslosigkeit; Vergleich